Metagenomic characterization of the cecal microbiota community and functions in finishing pigs fed fermented Boehmeria nivea - Liang, Xiaoxiao; Zhai, Zhenya; Ren, Fengyun; Jie, Yucheng; Kim, Soo-Ki; Niu, Kai-Min; Wu, Xin (Frontiers in Veterinary Science, 2023)
Ramie (Boehmeria nivea, BN) is used as livestock forage through silage fermentation owing to its nutritional value. To date, relatively few studies have investigated the effects of dietary fermented BN (FBN) on gut health in finishing pigs. The aim of the present study was to investigate the dietary effects of 20% FBN on intestinal morphology, gene expression, and the functional response of the gut microbiota in finishing pigs. We found that FBN did not significantly affect serum antioxidant enzyme activities, ileal morphology, or the expression of genes encoding antioxidant enzymes, inflammatory cytokines, or tight junction proteins in the liver of the pigs. However, the gene expression levels of aryl hydrocarbon receptor (AHR) and interleukin 6 (IL6) were significantly downregulated in the ileum. Metagenomic analysis demonstrated that, compared with that seen in the control group, the cecal microbiota of pigs in the FBN treatment group was more closely clustered, and contained a greater number of unique microbes. Bacteria were the predominant kingdom in the cecal microbiota, while Firmicutes, Bacteroidetes, and Proteobacteria were the dominant phyla, and Streptococcus, Lactobacillus, and Prevotella were the dominant genera. Dietary FBN significantly increased the abundance of the probiotic bacterium Roseburia inulinivorans. Functional analysis of the cecal microbiota showed that ABC transporter levels and glycolysis/gluconeogenesis-associated functions were diminished in FBN-fed pigs. Meanwhile, CAZyme analysis revealed that dietary FBN significantly downregulated the contents of carbohydrate-active enzymes, including GT2, GH1, GH25, and GH13_31. In addition, cytochrome P450 analysis revealed that CYP51 and CYP512 abundance was decreased with FBN treatment. An assessment of antibiotic resistance based on Comprehensive Antibiotic-Resistance Database (CARD) annotation indicated that the cecal microbes of pigs in the FBN treatment group had increased resistance against lincosamide, streptogramin, and chloramphenicol and reduced resistance against amikacin, isepamicin, neomycin, lividomycin, gentamicin, paromomycin, ribostamycin, and butirosin. Finally, virulence factor-related analysis showed that putative hemolysin-associated functions were reduced whereas fibronectin-binding protein, flagella, and alginate-associated functions were increased. Combined, our data showed that FBN supplementation exerted only minor effects on intestinal morphology and microbial community composition, suggesting that it is potentially safe for use as a supplement in the diets of finishing pigs.